PEMBERDAYAAN PEMUDA PUTUS SEKOLAH MELALUI PELATIHAN KETERAMPILAN TENUN IKAT DI SANGGAR DOKA TAWA TANA KABUPATEN SIKKA - Dua Lena, Maria Yesicha; Neonufa, Samrid; Selly, Frans Kristian (Universitas Nusa Cendana, 2024)
ABSTRACT Out-of-school youth need empowerment. The impact of young people not continuing their education is unemployment, lack of skills and detrimental treatment such as drug use. Out-of-school youth are also less likely to obtain stable employment and generate adequate income. The aim of this research is to determine the implementation of empowering out-of-school youth through ikat weaving skills training at Sanggar Doka Tawa Tana studio. The type of research used in this research is descriptive qualitative research. The results of the research show that: Empowering School Dropout Youth through ikat weaving skills training at Sanggar Doka Tawa Tana consists of 3 (three) stages, namely: 1) the awareness and behavior formation stage, 2) the ability transformation stage in the form of knowledge and skills and 3) the increasing intellectual abilities and skills to achieve independence. The result is that young people who drop out of school get motivation that can change their lives, increase their skills in the field of ikat weaving, take initiative in the process of gaining knowledge and skills, open business opportunities, and increase the independence of participants and also success in increasing their knowledge and skills in making sarongs. and improve family welfare.